Bounds on Spectral Radius and Signless Laplacian Spectral Radius for Generalized Core-satellite Graphs (European Journal of Pure and Applied Mathematics, 2025)
A Generalized core-satellite graph Θ(c, S, η∗) belongs to the family of graphs of diameter two. It has a central core of nodes connected to a few satellites, where all satellite cliques are not identical and might be of different sizes. These graphs can be used to model any real-world complex network. Using core-satellite graphs, properties like hierarchical structure can be conveniently modeled for large complex networks. In this paper, we obtain the lower and upper bounds for the spectral radius and signless Laplacian spectral radius of the generalized core-satellite graph, in terms of number of vertices, number of edges, and the graph parameters associated with the structure of the graph in both satellites and the core.
Keywords: Spectral radius; Signless Laplacian spectral radius; Generalised Coresatellite graphs